THE PLUTONIC-DYKE SYSTEM AND HOST LIGURIAN SUCCESSIONS OF THE ISLAND OF MONTECRISTO (TUSCAN ARCHIPELAGO, ITALY): NEW STRATIGRAPHIC, PETROGRAPHIC AND STRUCTURAL DATA - Giusti, Riccardo; Pandeli, Enrico; Colombo, Giulio; Elter, Franco Marco; Casalini, Martina; Orti, Letizia (Ofioliti, 2023)
To improve the geological knowledge of the poorly studied and scarcely accessible Island of Montecristo (Tuscan Archipelago), the Authors performed 1:5000 geological survey, meso- and microstructural study and petrographic analyses on the Messinian pluton, on the associated dyke/vein network and on the remnants of the hornfels cover occurring along the western and southern coasts. The results of this study allow: a) to define a complex system of dykes and hydrothermal veins crossing the pluton and its hornfels. b) to directly correlate the Montecristo hornfels rocks (here grouped in the “Cala S. Maria-Cala dei Ladri Unit”) with the contact metamorphic aureole of the Monte Capanne pluton of the Elba Island (i.e., the Punta Polveraia-Fetovaia Unit). The Cala S. Maria-Cala dei Ladri Unit is mainly composed of alternating metapelites and metasandstones (whose protolith is likely the Quartzarenitic Member of the Palombini Shales and/or the Val Lavagna Shales of Early-Late Cretaceous age) and of minor metaophiolitic rocks; metaserpentinites were also mapped for the first time. c) to recognize low-medium grade hornfels in the remnants of the contact metamorphic aureole and the ubiquitous presence of basal cataclastic horizons, testifying a role of “roof pendant” plates for the Cala S. Maria-Cala dei Ladri Unit outcrops. d) to reconstruct a complex structural evolution for the emplacement of the pluton and for its contact metamorphic aureole. This evolution started with ductile events, i.e., formation of mylonite in the granitoids and of a pervasive S1 schistosity in the hornfels, which was likely related to flattening processes occurred during the balooning of the magmatic body, followed by ductile D2 folding with the detachment of the recrystallized Ligurian covers due to the rise of the partially cooled pluton, and then by a series of jointing/faulting events, whose lineaments were used as pathways for the intrusion of the different dykes and hydrothermal veins; finally, a NW-SE striking transtensive sinistral shear zone (Cala Maestra-Cala Corfù Fracture Zone) with an about ENE-WSW directed s1 originated in the south/south-western part of the island. This shear zone represents one of the few witness of regional transcurrent structures in the Tuscan Archipelago and was likely active also during the emplacement of the plutonic body.